Beauty Bias? Exploring the Influence of Attractiveness on Conservation Intentions for Plants and Their Pollinators - Pavol Prokop; Simona Todáková; Jana Fančovičová (Diversity)
Plants are an essential component of ecosystems; however, their significance is frequently underestimated, resulting in less effective conservation efforts. One approach to address plant blindness (PB) or plant awareness disparity (PAD) is to establish connections between plants and animals, as animals inherently attract more human attention. In this study, we employed an online questionnaire to manipulate visual materials featuring plant flowers alone, plant flowers accompanied by pollinators, and pollinators in isolation. We assessed participants’ willingness to protect (WTP) and the perceived attractiveness of both plants and their pollinators. Our findings revealed that pollinators presented alone received higher WTP scores than plants. Moreover, the visual association between pollinators and plants enhanced WTP plants. Conversely, plants were consistently perceived as more attractive than pollinators, irrespective of whether the flowers were displayed alone or alongside pollinators. The perceived attractiveness of both plants and pollinators was significantly correlated with WTP. Notably, colourful pollinators such as Selasphorus rufus, Vestiaria coccinea, and Danaus plexippus positively influenced WTP plants, while the remaining five species (predominantly invertebrates) did not exhibit a similar effect. We propose that establishing a connection between visually appealing pollinators and plants can help mitigate PB/PAD. These pollinators should be utilised as umbrella species to enhance human attention and interest in pollination processes and plant biology.